The Dynamics of Islamic Education for The Chinese Muslim Minority in West Sumatra - Harmonedi, Harmonedi; Awiskarni, Awiskarni; Kurnia, Asraf; Zalnur, Muhammad; Basit, Abdul; Tamrin, M. (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2025)
Islamic education for the Chinese Muslim minority in West Sumatra is a process fraught with challenges while offering significant opportunities in a multicultural society. This study aims to explore the supporting and inhibiting factors influencing the implementation of Islamic education in this community and to formulate strategies for optimizing its potential. Utilizing a qualitative approach, the research employed in-depth interviews, direct observation, and literature analysis. The participants consisted of 15 Chinese Muslims (8 males and 7 females), aged between 25 and 60 years, including community leaders, educators, parents, and youth actively involved in Islamic educational settings in Padang and Payakumbuh. The findings reveal that social support from the local community, the presence of inclusive educational institutions, the role of organizations like PITI, and family economic stability are key supporting elements. However, the community faces significant challenges, including social discrimination, lack of support from formal institutions, difficulties in cultural integration, and limited awareness of the importance of religious education. This study recommends a collaborative approach between the government, educational institutions, and society to create a more inclusive educational ecosystem. Such efforts are expected to strengthen the Islamic identity of Chinese Muslims and encourage their active participation in a pluralistic society.